2021
DOI: 10.1002/j.2769-2795.2021.tb00081.x
|View full text |Cite
|
Sign up to set email alerts
|

Difference between remimazolam toluenesulfonic acid and propofol in waking quality and conscious state after general anesthesia

Abstract: ObjectiveTo explore the difference of anesthesia recovery and postoperative conscious state between remimazolam toluenesulfonic acid and propofol after induction and maintenance of general anesthesia.Methods104 patients undergoing elective tracheal intubation general anesthesia in our hospital were randomly divided into 2 groups: Remimazolam Toluenesulfonic acid group (Group R) and Propofol group (Group P). MOAA/S score, the modified Aldrete score, recovery index, time point, a state of consciousness, interpre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(16 citation statements)
references
References 35 publications
0
14
0
Order By: Relevance
“…Our results demonstrated no difference in extubation time (MD = −4.59 min, 95% CI -12.31 to 3.13, p = 0.24; I 2 = 98%; four RCTs; n = 485) (Supplementary Figure S3A) (Doi et al, 2020;Li et al, 2021a;Tang et al, 2021;Shi et al, 2022) and time to eye opening (MD = −1.12 min, 95% CI -7.38 to 5.14, p = 0.73; I 2 = 100%; three RCTs; n = 405) (Supplementary Figure S3B) (Doi et al, 2020;Li et al, 2021a;Shi et al, 2022) between the two groups. The incidence of PONV was available in five trials (Li et al, 2021a;Dai et al, 2021;Tang et al, 2021;Hari et al, 2022;Shi et al, 2022), which demonstrated comparable risk of PONV in both groups (RR = 0.82, 95% CI: 0.26 to 2.6, p = 0.74, I 2 = 0%, five trials, 419 participants) (Supplementary Figure S4). While subgroup analysis showed no significant impact of the type of surgery on extubation time and PONV, it was not performed on time to eye opening as only trials of non-cardiac surgery were available.…”
Section: Recovery Characteristics Between Remimazolam and Propofolmentioning
confidence: 65%
See 4 more Smart Citations
“…Our results demonstrated no difference in extubation time (MD = −4.59 min, 95% CI -12.31 to 3.13, p = 0.24; I 2 = 98%; four RCTs; n = 485) (Supplementary Figure S3A) (Doi et al, 2020;Li et al, 2021a;Tang et al, 2021;Shi et al, 2022) and time to eye opening (MD = −1.12 min, 95% CI -7.38 to 5.14, p = 0.73; I 2 = 100%; three RCTs; n = 405) (Supplementary Figure S3B) (Doi et al, 2020;Li et al, 2021a;Shi et al, 2022) between the two groups. The incidence of PONV was available in five trials (Li et al, 2021a;Dai et al, 2021;Tang et al, 2021;Hari et al, 2022;Shi et al, 2022), which demonstrated comparable risk of PONV in both groups (RR = 0.82, 95% CI: 0.26 to 2.6, p = 0.74, I 2 = 0%, five trials, 419 participants) (Supplementary Figure S4). While subgroup analysis showed no significant impact of the type of surgery on extubation time and PONV, it was not performed on time to eye opening as only trials of non-cardiac surgery were available.…”
Section: Recovery Characteristics Between Remimazolam and Propofolmentioning
confidence: 65%
“…Our results showed a significantly lower risk of hypotension associated with the use of remimazolam than that with propofol [Risk ratio (RR) = 0.57, 95% CI: 0.43 to 0.75, p < 0.0001, I 2 = 12%, five trials, 564 participants) (Figure 3) (Doi et al, 2020;Li et al, 2021a;Dai et al, 2021;Liu et al, 2021;Shi et al, 2022). Compared with propofol, the use of remimazolam as an induction agent correlated with a higher heart rate [Mean difference (MD) = 4.26 beats/minutes, 95% CI: 0.01 to 8.51, p = 0.03, I 2 = 61%, four trials, 265 participants] (Supplementary Figure S1) (Dai et al, 2021;Liu et al, 2021;Hasegawa et al, 2022;Shi et al, 2022).…”
Section: Changes In Hemodynamic Profiles Between Remimazolam and Prop...mentioning
confidence: 71%
See 3 more Smart Citations